1984
DOI: 10.1128/mcb.4.8.1591
|View full text |Cite
|
Sign up to set email alerts
|

Discontinuous DNA replication of Drosophila melanogaster is primed by octaribonucleotide primer.

Abstract: To investigate the precise structure of eucaryotic primer RNA made in vivo, short DNA chains isolated from nuclei of Drosophila melanogaster embryos were analyzed. Post-labeling of 5' ends of short DNA chains with polynucleotide kinase and [_Y-32P]ATP revealed that 7% of the DNA fragments were covalently linked with mono-to octaribonucleotide primers at their 5' ends. Octaribonucleotides, the major component (ca. 30%), formed the cap structure in the reaction with vaccinia guanylyltransferase and [o-32P]GTP, i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
9
0

Year Published

1985
1985
2013
2013

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(10 citation statements)
references
References 18 publications
(41 reference statements)
1
9
0
Order By: Relevance
“…The 5' residue is also a purine (A: G ration 2 4). Sequence analysis of the SV40 primers showed that discontinuous DNA replication occurs exclusively on the lagging strand relatively to the origin of the viral genome [34, 351. More recently, the size and the composition of primers isolated from Drosophilu embryos have been investigated [36]. The authors used vaccinia guanylyltransferase to label intact nascent DNA fragments having a 5'-di-or triphosphate group to discriminate them from partially hydrolyzed primers.…”
Section: Churucteristics Oj' Primers In Vivomentioning
confidence: 99%
See 2 more Smart Citations
“…The 5' residue is also a purine (A: G ration 2 4). Sequence analysis of the SV40 primers showed that discontinuous DNA replication occurs exclusively on the lagging strand relatively to the origin of the viral genome [34, 351. More recently, the size and the composition of primers isolated from Drosophilu embryos have been investigated [36]. The authors used vaccinia guanylyltransferase to label intact nascent DNA fragments having a 5'-di-or triphosphate group to discriminate them from partially hydrolyzed primers.…”
Section: Churucteristics Oj' Primers In Vivomentioning
confidence: 99%
“…Yoda and Okazaki [53] demonstrated that primase activity in a cytoplasmic extract of D. melanogaster embryos synthesizes hexa-to heptaribonucleotides. Primers synthesized in vitro could be one or two nucleotides shorter than their counterparts in vivo [36,531. Primers synthesized on homopolymers in the absence of the complementary dNTP are longer.…”
Section: Characteristics Of Primers Synthesized In Vitromentioning
confidence: 99%
See 1 more Smart Citation
“…As explained for mSVO2, the combined data revealed that the lengths of nascent chains derived by a direct comparison with the lengths of sequenced DNA chains had to be shortened by 6.5 bases in the case of mSVO9 and 7 bases in the case of mSVO7 to locate the actual initiation sites. Positions of 15 major sites on mSVO9 DNA and 14 major sites on mSVO7 DNA are provided in Fig. 4.…”
mentioning
confidence: 99%
“…Although little is known about the molecular mechanisms that regulate entry of eucaryotic cells into the S phase, substantial genetic and biochemical evidence (reviewed in references 7, 10, and 14) suggests that replication is initiated at specific sites (or origins of replication) and proceeds bidirectionally (10) in a semidiscontinuous fashion (19). Selection of those replicons slated to be synthesized immediately upon entry into the S phase may be regulated at the level of either initiation or elongation, perhaps by the interaction of trans-acting initiation factors with specific origin sequences or by differential elongation of performed initiation complexes.…”
mentioning
confidence: 99%